PP.13.02: THE PROGNOSTIC VALUE OF ENDOTHELIAL DYSFUNCTION AT HYPERTENSIVE PATIENTS WITH OR WITHOUT DIABETES MELLITUS. (June 2015) - Gavrila, A.; Florea, M.; Ciobanu, M.; Chirion, M.; Mogosanu, C.; Pritulescu, C.; Marinescu, S.; Sosea, I.; Persu, R.; Rosu, A.
Abstract : Objective: The objective of the study was to estimate how the endothelial dysfunction (ED) correlates with cardiovascular and renal events at hypertensive patients (pts) with or without diabetes mellitus (DM). Design and method: 30 hypertensive pts (mean age = 58.2 ± 7.6 years, 53.3% males)-group 1 and 30 hypertensive pts with DM, matched for age and sex (mean age = 59.8 ± 7.3 years, 56.6% males)-group 2. ED was evaluated using ultrasound assessment of flow-mediated vasodilatation (FMD) of the brachial artery. FMD smaller than 10% was considered abnormal. All pts were evaluated during one year, in order to detect the following complications: unstable angina (UA), non-ST-segment elevation myocardial infarction (NSTEMI), ischemic stroke (IS), renal dysfunction (RD): microalbuminuria, proteinuria, chronic kidney disease. Results: In group 1, 13 pts (43.3%) had reduced FMD: 7.6 ± 1.5%. In group 2, 16 patients (53.3%) had reduced FMD: 6.3 ± 2.1%. The difference is not significantly statistic between the two groups (p = 0.07). In group 1, UA was significantly associated with reduced FMD (7.1 ± 1.5% vs 11.3 ± 2.2%, p = 0.03). In the same group, RD was found in a significantly higher proportion at patients with reduced FMD (7.8 ± 1.8% vs 12.1 ± 2.3%, p = 0.02). In group 2, UA was also significantly associated with reduced FMD (6.8 ± 2.1% vs 10.9 ± 2.8%, p = 0.01). NSTEMI was significantly more frequent at pts with reduced FMD (6.3 ± 1.7% vs 11.4 ± 3.1%, p = 0.01). In the same group, RD was found in a significantly higher proportion at pts with reduced FMD (6.9 ± 2.7% vs 10.5 ± 2.6%, p = 0.02). Conclusions: Hypertensive pts with DM have ED in a greater, but not significant proportion than hypertensive pts without DM. ED seems to predict a worse mid term outcome (one year) concerning cardiovascular and renal events at hypertensive pts, especially with DM. Moreover, ED appears to have more powerful mid term prognostic value for incidence of acute coronary syndromes without ST-segment elevation at hypertensive pts with DM.